An atomistic mechanism for elasto-plastic bending in molecular crystals. Issue 13 (8th March 2023) - Bhattacharya, Biswajit; Michalchuk, Adam A. L.; Silbernagl, Dorothee; Yasuda, Nobuhiro; Feiler, Torvid; Sturm, Heinz; Emmerling, Franziska
Abstract : Mechanically flexible single crystals of molecular materials offer potential for exciting new directions in advanced materials design. Unravelling the mechanisms of this fascinating bending phenomenon is needed and developed here. Abstract : Mechanically flexible single crystals of molecular materials offer potential for a multitude of new directions in advanced materials design. Before the full potential of such materials can be exploited, insight into their mechanisms of action must be better understood. Such insight can be only obtained through synergistic use of advanced experimentation and simulation. We herein report the first detailed mechanistic study of elasto-plastic flexibility in a molecular solid. An atomistic origin for this mechanical behaviour is proposed through a combination of atomic force microscopy, μ-focus synchrotron X-ray diffraction, Raman spectroscopy, ab initio simulation, and computed elastic tensors. Our findings suggest that elastic and plastic bending are intimately linked and result from extensions of the same molecular deformations. The proposed mechanism bridges the gap between contested mechanisms, suggesting its applicability as a general mechanism for elastic and plastic bending in organic molecular crystals.